2021
DOI: 10.18178/ijiet.2021.11.6.1522
|View full text |Cite
|
Sign up to set email alerts
|

Hands-on Making Leather Goods: Learning from YouTube Videos

Abstract: YouTube is the world’s most popular video platform, which not only provides entertainment videos, but also allows many professional or amateur teachers to upload teaching videos for users to learn specific skills. However, most of the current research focuses on the effectiveness of YouTube for formal learning. In the perspective of cognitive-affective theory of learning with media (CATLM), the informal learning model through YouTube can also be regarded as a meaningful learning method. Therefore, based on CAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Local wisdom-based educational films improve student motivation, learning outcomes, and self-identity [57][58][59][60]. Integration is one method for addressing existing flaws.…”
Section: B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local wisdom-based educational films improve student motivation, learning outcomes, and self-identity [57][58][59][60]. Integration is one method for addressing existing flaws.…”
Section: B Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that combining movies and learning can improve student motivation, learning competency, and learning outcomes [57][58][59][60]. However, there are some drawbacks to using learning movies, including relatively high production costs and a lack of flexibility in adapting film content to different learning needs and conditions, erratic and unfocused behavior while learning, delaying learning at will, and interaction with others while using educational films [19,61].…”
Section: Educational Filmsmentioning
confidence: 99%
“…Furthermore, the study's findings provide an overview of students' perceptions of using YouTube to regulate their learning and to enhance their English skills. Furthermore, it is thought that learning English on YouTube is more enjoyable, fascinating, and adaptable than formal classroom learning (Lestari et al, 2019); (Yusri et al, 2018); (Maziriri et al, 2020); (Zaidi et al, 2018); (Wang, 2021).…”
Section: Youtube For Enhancing Students' Motivation and Self-regulate...mentioning
confidence: 99%
“…Recent studies have focused on using YouTube as Digital Learning Media in ELT to enhance student's general learning skills, autonomous learning, self-motivation, and confidence (Yusri et al, 2018;Lestari et al, 2019;Putri, 2019;Maziriri et al, 2020;Wang et al, 2021) in some ways of implementation (Atmojo & Priyo, 2020;Amaliah, 2021;Bardakci, 2019;Murni, et al, 2021;Ariantini., et.al, 2021;Sakkir et al, 2020;Yusuf, 2020;Abbas, N., F.& Qassim, T., 2020;Srinivasacharlu, 2020;Saban, 2020;Nasution, 2019;Latifah, 2019). YouTube has been argued to enhance students' listening skills (Chien et al, 2020;Istifci & Dogan Ucar, 2021, Saputra, Y., & Fatimah, 2018, improve students' speaking skills (Shofatunnisa et al, 2021;Sari et al, 2020;Balbay & Kilis, 2017;Albahlal, 2019;Saed et al, 2021;Binmahboob, 2020;Rusgandi, Ali Ashari, 2019;Sari, 2018) while supporting their writing and reading skill (Olasina, 2017;Alobaid, 2020;Noortyani Rusma, 2019), in more bilingual learning (Poramathikul et al, 2020;Listiani et al, 2021) with more independent and self-regulated learning (Latifah, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…YouTube is a website for video-sharing created in February 2005 by three former PayPal employees, and it allows users to share or upload videos and watch (Hopkin, 2006in Wikipedia, 2023. In several new studies, general learning skills, autonomous learning, self-motivation, and self-confidence of EFL learners can be improved through digital learning media, namely the YouTube platform (Yusri et al, 2018;Lestari et al, 2019;Maziriri et al, 2020;Wang et al, 2021;Audina et al, 2022;in Aprianto, 2023). In short, YouTube is an alternative media for young bilingual learners that can influence language skills, self-motivation, and self-regulation of learning (Widiantari et al, 2023in Aprianto, 2023.…”
Section: Youtubementioning
confidence: 99%